2009
DOI: 10.1016/j.jacc.2009.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Activating Autoantibodies to the Beta-1 Adrenergic and M2 Muscarinic Receptors Facilitate Atrial Fibrillation in Patients With Graves' Hyperthyroidism

Abstract: Objectives We studied activating autoantibodies to β1-adrenergic (AAβ1AR) and M2 muscarinic receptors (AAM2R) in the genesis of atrial fibrillation (AF) in Graves’ hyperthyroidism. Background AF frequently complicates hyperthyroidism. AAβ1AR and AAM2R have been described in some patients with dilated cardiomyopathy and AF. We hypothesized their co-presence would facilitate AF in autoimmune Graves’ hyperthyroidism. Methods IgG purified from 38 patients with Graves’ hyperthyroidism with AF (n=17) or sinus rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
70
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 24 publications
7
70
0
2
Order By: Relevance
“…It will be important to elucidate in future studies the precise molecular mechanism how antibodies against these receptors induced a similar phenotypes. Nevertheless, anti-M 2 R antibodies have also been implicated in two additional human diseases, sinus node dysfunction [37] and atrial fibrillation [38,39]. It is thus possible that mechanisms similar to what we observe in our mouse model are operative in humans.…”
supporting
confidence: 68%
“…It will be important to elucidate in future studies the precise molecular mechanism how antibodies against these receptors induced a similar phenotypes. Nevertheless, anti-M 2 R antibodies have also been implicated in two additional human diseases, sinus node dysfunction [37] and atrial fibrillation [38,39]. It is thus possible that mechanisms similar to what we observe in our mouse model are operative in humans.…”
supporting
confidence: 68%
“…Antibodies for two specific cardiac GPCRs, the b 1 -AR and the M 2 mAChR, are a common feature. IgGs targeting and activating either or even both receptors simultaneously (Elies et al, 1996) have been isolated in patients with idiopathic cardiomyopathy (Wallukat and Wollenberger, 1987;Fu et al, 1993), peripartum cardiomyopathy (Warraich et al, 2005;Stavrakis et al, 2009;Stavrakis et al, 2011;Liu et al, 2014), and in Chagas-induced cardiomyopathy (Sterin-Borda et al, 1976;Borda et al, 1984;Elies et al, 1996;Wallukat et al, 2010;Muñnoz-Saravia et al, 2012).…”
Section: Allosteric Autoantibodiesmentioning
confidence: 99%
“…2,3 Studies with transgenic mouse models have revealed that deregulation of the cyclic AMP-regulated protein kinase A (cAMP/PKA) pathway can cause apoptosis. 4 Specifically, badrenergic receptor (bAR) activation by catecholamines or autoantibodies, as seen in Grave's disease, 5 can cause PKAmediated cardiomyocyte apoptosis, resulting in heart failure (HF). 6 Furthermore, administration of catecholamines, such as epinephrine, is often the last resort for treatment of patients suffering from septic shock, 7 and this is associated with profound alterations in immune function, similar to those observed in haemorrhagic shock where all lymphocyte subsets are decreased owing to excessive apoptosis.…”
mentioning
confidence: 99%